bahasa Inggris untuk SLTP I kelas 1 sesuai dengan kurikulum 1994 Y. mei Setiyanta, M.A. Titik Setyaningsih, Ag. Linmy Indarti - SETIYANTA, Y. Mei; Setyaningsih, M.A. Titik; Indarti, Ag Linmy
108 hlm. ilus. 28 cm